Prevalence of latent tuberculosis infection and incidence of active tuberculosis in school close contacts in Shanghai, China: Baseline and follow-up results of a prospective cohort study - Xiao, Xiao; Chen, Jing; Jiang, Yue; Li, Peng; Li, Jin; Lu, Liping; Zhao, Yameng; Tang, Lihong; Zhang, Tianyuan; Wu, Zheyuan; Rao, Lixin; Yuan, Zheng’an; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Background: The management of latent tuberculosis infection (LTBI) is a key action for the realization of the “End tuberculosis (TB) Strategy” worldwide, and it is important to identify priority populations. In this prospective cohort study, we evaluated the prevalence of LTBI and incidence of active TB among close contacts and explored the suitable TB control strategy in schools. Methods: We designed a cohort with 2 years of follow-up, recruiting freshman/sophomore TB patients’ close contacts from three administrative districts in Shanghai. These were chosen based on different levels of TB incidence reported in 2019. Questionnaires were included and all participants received both tuberculin skin test (TST) and QuantiFERON-TB Gold (QFT) at baseline, then tracked the outcomes of them during the follow-up period. Results: The prevalence of LTBI was 4.8% by QFT. Univariate analysis showed that the risk of LTBI was higher in those contacting etiology-positive patients or did not have BCG scars, including smokers. The risk increased with poor lighting and ventilation conditions at contact sites. Multivariate analysis showed that those contacting with etiology-positive patients (OR=4.180; 95%CI, 1.164-15.011) or who did not have BCG scars (OR=5.054; 95%CI, 2.278-11.214) had a higher risk of being LTBI, as did the current smokers (OR=3.916; 95%CI, 1.508-10.168) and those who had stopped smoking (OR=7.491; 95%CI, 2.222-25.249). During the 2-year follow-up period, three clinically diagnosed cases of TB were recorded, the 2-year cumulative incidence was 0.4% (95%CI 0.1-1.2), the median duration for TB occurrence was 1 year, the incidence rate of active TB was 2.0 per 1000 person-years with a total of 1497.3 observation person-years. For those LTBI, no one initiated preventive treatment, in the QFT (+) cohort, 1 TB case was observed, 71 person-years with an incidence rate of 14.1 14.1 (95%CI 2.5-75.6) per 1000 person-years, in the TST (+++) cohort, 2 TB cases were observed 91.5 person-years with an incidence rate of 21.9 (95%CI 6.0-76.3) per 1000 person-years. Conclusions: The results suggest that school close contacts are one of the key populations for LTBI management. Measures should be taken to further reduce the prevalence of LTBI and the incidence of active TB among them.